Acceptability, Usefulness, and Ease of Use of an Enhanced Video Directly Observed Treatment System for Supporting Patients With Tuberculosis in Kampala, Uganda: Explanatory Qualitative Study - Sekandi, Juliet Nabbuye; McDonald, Adenike; Nakkonde, Damalie; Zalwango, Sarah; Kasiita, Vicent; Kaggwa, Patrick; Kakaire, Robert; Atuyambe, Lynn; Buregyeya, Esther (JMIR Publications, 2023)
Abstract BACKGROUNDIn tuberculosis (TB) control, nonadherence to treatment persists as a barrier. The traditional method of ensuring adherence, that is, directly observed therapy, faces significant challenges that hinder its widespread adoption. Digital adherence technologies such as video directly observed therapy (VDOT) are emerging as promising solutions. However, as these novel technologies gain momentum, a critical gap is the lack of comprehensive studies evaluating their efficacy and the unique experiences of patients in Africa.OBJECTIVEThe aim of this study was to assess patients' experiences that affected acceptability, usefulness, and ease of use with an enhanced VDOT system during monitoring of TB treatment.METHODSWe conducted individual open-ended interviews in a cross-sectional exit qualitative study in Kampala, Uganda. Thirty participants aged 18-65 years who had completed the VDOT randomized trial were purposively selected to represent variability in sex, adherence level, and HIV status. We used a hybrid process of deductive and inductive coding to identify content related to the experience of study participation with VDOT. Codes were organized into themes and subthemes, which were used to develop overarching categories guided by constructs adapted from the modified Technology Acceptance Model for Resource-Limited Settings. We explored participants' experiences regarding the ease of use and usefulness of VDOT, thereby identifying the facilitators and barriers to its acceptability. Perceived usefulness refers to the benefits users expect from the technology, while perceived ease of use refers to how easily users navigate its various features. We adapted by shifting from assessing perceived to experienced constructs.RESULTSThe participants' mean age was 35.3 (SD 12) years. Of the 30 participants, 15 (50%) were females, 13 (43%) had low education levels, and 22 (73%) owned cellphones, of which 10 (45%) had smartphones. Nine (28%) were TB/HIV-coinfected, receiving antiretroviral therapy. Emergent subthemes for facilitators of experienced usefulness and ease of VDOT use were SMS text message reminders, technology training support to patients by health care providers, timely patient-provider communication, family social support, and financial incentives. TB/HIV-coinfected patients reported the added benefit of adherence support for their antiretroviral medication. The external barriers to VDOT's usefulness and ease of use were unstable electricity, technological malfunctions in the app, and lack of cellular network coverage in rural areas. Concerns about stigma, disease disclosure, and fear of breach in privacy and confidentiality affected the ease of VDOT use.CONCLUSIONSOverall, participants had positive experiences with the enhanced VDOT. They found the enhanced VDOT system user-friendly, beneficial, and acceptable, particularly due to the supportive features such as SMS text message reminders, incentives, technology training by health care providers, and family support. However, it is crucial to address the barriers related to technological infrastructure as well as the privacy, confidentiality, and stigma concerns related to VDOT. MEDLINE - Academic
Keywords: digital adherence technologies; tuberculosis; video directly observed therapy; acceptability; directly observed therapy; DOT; Uganda; treatment; digital; technology acceptance model; social support; privacy; stigma